2013
DOI: 10.1111/ijn.12141
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and risk of pressure ulcer in adult intensive care unit patients

Abstract: The objective of this study was to assess relationship between smoking, some other risk factors and ulcers development in intensive care unit. This prospective cohort study was performed in two university-affiliated hospitals. The sample consisted of adult male patients who were admitted to medical-surgical intensive care units. All eligible patients were grouped according to their cigarette smoking status as smoker and non-smoker. The final sample included 160 smokers and 192 non-smokers. Pressure ulcer occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
2
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
4
33
2
8
Order By: Relevance
“…Pressure ulcers are often associated with comorbidities that disrupt tissue perfusion, including diabetes, hypertension, and non‐specific cardiac issues . Similarly, in our study, we found anaemia, hypertension, and respiratory disease to be significant.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Pressure ulcers are often associated with comorbidities that disrupt tissue perfusion, including diabetes, hypertension, and non‐specific cardiac issues . Similarly, in our study, we found anaemia, hypertension, and respiratory disease to be significant.…”
Section: Discussionsupporting
confidence: 80%
“…Most of the studies agreed that pressure ulcers occurred commonly in older patients, but only Wright et al found decreasing age to be associated with HAPU; however, Wright's study had a much smaller sample size (N = 88), and hence, it may be under‐powered to detect statistical significance. There were also studies that did not find older age to be significantly associated with HAPU, but their study population's mean age was between 48 and 58 years.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, international studies in ICU have shown PU incidence coefficients of PU between 3.2% and 39.0% (13)(14)(15)(16)(17) . In post-op cardiac surgery patients (18) , an incidence of 16.4% was found.…”
Section: Discussionmentioning
confidence: 99%
“…National studies show a great variation either in PU incidence coefficients found in critical patients (10.0% to 62.5%) (11)(12) or in the evaluation periods (1 to 15 months) (11,12) . International studies show PU incidence in ICU between 3.2% and 39.0% (13)(14)(15)(16)(17) . Considering that critical patients are highly vulnerable to the development of skin injuries and that these injuries involve specific risk factors, depending on the underlying disease and associated conditions, this study was conducted to identify and analyze the incidence coefficients of PU and the risk factors for PU development in cardiopulmonary intensive care unit patients.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, studies involving critical patients have pointed to PI incidence ranging from 3.3% to 39% [3, 4]. A literature review of European studies spanning from 2000 to 2005 identified that the PI incidence varied from 3.8% to 12.4% [5].…”
Section: Introductionmentioning
confidence: 99%